Etika Hiburan dalam Perspektif Hadis: Analisis terhadap Aplikasi TikTok - Husna, Arinal; Suparwany, Suparwany; Roslaili, Yuni (DEPARTEMENT OF COMMUNICATION AND ISLAMIC BROADCASTING STUDIES, 2023)
The TikTok application is an entertainment medium that allows its users to do freestyle, such as dance, lip sync, challenges, etc., which was once banned in Indonesia because it contained negative content. This study discusses the ethics of entertainment from a hadith perspective, with the main focus being the TikTok application media. This qualitative research is library research with a descriptive analysis approach. The theory used is thematic hadith theory. The thematic hadith method is carried out by tracing the hadiths using the lafadz